(untitled) (Global Journal of Science Frontier Research, 2017)
In this note, we give expressions for the first(second) Zagreb coindex, second Zagreb index(coindex), third Zagreb index and first hyper-Zagreb index of the line graphs of subdivision graphs of 2D-lattice, nanotube and nanotorus of TUC 4 C 8 [p, q] and obtain upper bounds for Wiener index and degree-distance index of these graphs. This note continue the program of computing certain topological indices of the line graphs of subdivision graphs of 2D-lattice, nanotube and nanotorus of TUC 4 C 8 [p, q] [25] [M. F.